Managing a digital archiving project at the University of the West Indies Library: a case study (Libellarium: journal for research in the field of information and related sciences, 2017)
Digital archiving presents a ready solution to the problem of hidden special collections. The availability of information and communication technology solutions provide libraries, archives and museums with a way forward. However, cost constraints present a real challenge to institutions, especially in the developing world where digitization projects must compete for scarce resources with many other pressing services. In the competition for resources special collections sometimes play second fiddle to immediate services, for example user facilities.The Library of the University of the West Indies (UWI), Mona, faced with limited and declining financial resources, yet recognizing the value of its growing but hidden special collections especially to scholarship at the university, as well as to the cultural and historical significance of the Caribbean region, sought cost-effective and innovative solutions to address the situation and to go ‘global’ with these collections.This paper uses a case study approach and details the strategies employed by a team at the University of the West Indies, Mona Library, including the acquisition of equipment, selection of collections to be included, and digitization of thirty collections of varied formats as well as deliberate collaborative initiatives at training of staff to ensure sustainability. It discusses challenges in the on-going process, and complications alluded to by Prochaska (2009) especially those of legal issues, politics, ownership, and values involved in stewardship of the collections. The paper posits solutions against a background of scarce resources as well as opportunities for far reaching and effective services.
Keywords: Digitization; Special Collections; University of the West Indies Mona; Digital Curation; Hidden Collections